2017
DOI: 10.3389/fmicb.2017.02197
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Tyrosine Phosphorylation of UV-Activated EGFR by the Beta-Human Papillomavirus Type 8 E6 Leads to Papillomatosis

Abstract: Epidemiological evidence is accumulating that beta-human papillomaviruses (HPV) synergize with UV-light in the development of precancerous actinic keratosis, and cutaneous squamous cell carcinomas (cSCC), one of the most common cancers in the Caucasian population. We previously demonstrated the tumorigenic activity of beta-HPV type 8 (HPV8) in the skin of transgenic mice and its cooperation with UV-light. Analysis of underlying mechanisms now showed that in keratinocytes expressing the HPV8E6 protein a transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…Of β-HPV's genes, β-HPV E6 is the most well characterized [25]. It alters multiple cell signaling pathways including MAML1, TGFβ, NOTCH and EGFR signaling [26][27][28]. It also binds and destabilizes the cellular histone acetyltransferase, p300 [29].…”
Section: Introductionmentioning
confidence: 99%
“…Of β-HPV's genes, β-HPV E6 is the most well characterized [25]. It alters multiple cell signaling pathways including MAML1, TGFβ, NOTCH and EGFR signaling [26][27][28]. It also binds and destabilizes the cellular histone acetyltransferase, p300 [29].…”
Section: Introductionmentioning
confidence: 99%
“…Of β-HPV's genes, β-HPV E6 is the most well characterized [24]. It alters multiple cell signaling pathways including MAML1, TGFβ, NOTCH and EGFR signaling [25][26][27]. It also binds and destabilizes the cellular histone acetyltransferase, p300 [28].…”
Section: Introductionmentioning
confidence: 99%
“…Now we extended these studies and analyzed an effect of HPV8E6 on the level of endogenous PTPH1 present in various HPV8E6 expressing immortalized human keratinocyte cell lines and in NHEK. All these keratinocytes have been transduced with recombinant retroviruses expressing HPV8E6 or empty vector pLXSN [22]. Immunoblotting revealed that HaCaT, RTS3b as well as NHEK had higher amounts of endogenous PTPH1 when HPV8E6 was expressed (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that HPV8E6 stimulates the receptor-tyrosine kinase (RTK) activity of the epidermal growth factor receptor (EGFR) in response to UV-irradiation. This activity by HPV8E6 was crucial for the UV-induced development of skin papillomas in K14-HPV8E6 transgenic mice indicating that E6 enhances the effect of UV-light at the level of EGFR [22]. Our earlier work also showed that HPVE6 proteins can bind to the protein-tyrosine-phosphatase H1 (PTPH1) [23].…”
Section: Introductionmentioning
confidence: 99%